Análise dos conflitos de trânsito no centro de Pau dos Ferros-RN - Araújo, Igor Ferreira de (Universidade Federal Rural do Semi-Árido, 2019)
To the expansion of urban environments and the demographic, mobility has become a factor of importance for the quality of life and for the development of the country. However, the absence of a system leads to the emergence of legal transport systems in order to compromise the safety of roads and citizens. Thus, this study aimed to evaluate the points of view of the flow of vehicles in the center of the municipality of Pau dos Ferros / RN. For this purpose, bibliographical consultations were used; field survey, for the counting of the vehicles that circulate in the city; and a vectorization followed by the identification of the flows of vehicles. An area covered, located in the central region of the city of Pau dos Ferros, located in the semi-arid potential, by the study of traffic of cars, motorcycles, heavy vehicles and pedestrians. However, there is a lack of signaling and a disregarded exposure with pedestrians, since the adequacies for this group were not found. In the research were analyzed six conversions through which they traveled during the count period of 1,424 vehicles. Thus, the occurrence is an occurrence of unfolding, which contributes to a high number of collision possibilities. In this way, it is proposed the implementation of a roundabout that eliminates the best ordering of vehicular and pedestrian traffic. However, more detailed studies on the topography and drainage of the intervention area. The implementation of signaling is also a measure to be employed.
Keywords: Mobilidade; Tráfego urbano; Conflitos no trânsito; Mobility; Urban traffic; Conflicts in traffic; ENGENHARIAS::ENGENHARIA CIVIL